Foundations of Communication/Media/Digital (In)justice. Issue 4 (2nd November 2021) - Fuchs, Christian
ABSTRACT: The task of this article is to outline foundations of a Marxist-humanist approach to communication justice, media justice, and digital justice. A dialectical approach to justice is outlined that differs from idealist monism, dualism, and pluralism. It conceives of injustice as alienation and inhumanity and justice as humanism. This approach is applied to communication, media, and the digital. The article outlines concepts and dimensions of (in)justice in general, communication (in)justice, media (in)justice, and digital (in)justice.